Dominant Mode Design of Third-Order Linear Control Systems: Part 1 - A. Asbury (Measurement + Control, 1973)
The method of design involves three steps: Choose a closed loop system with the aid of contour plots of the performance criteria. Obtain the poles of the open loop inferred by the chosen system. Provide a synthesised transfer function which will correct the actual open loop to the form given by (2). This paper deals with (1) and provides the contour plots for: Time to 90% and to cross over. Time to within 1%. Overshoot and undershoot. Maximum rate. Velocity error constant. Bandwidth. Phase and gain margin. These are plotted against c and k where c is the ratio of real pole abscissa to the real part of the dominant complex poles and k is the ratio of the imaginary to the real part of the complex poles. A preferred region is defined which will be suitable for many industrial applications.